Books, Type and Cyprus. A Cyprological Book Archive - Panayides, Omiros (My University, 2023)
The presentation will be about the online archive Books, Type and Cyprus. An online open resource, functioning as a Design Archive, providing access to nearly 400 books that were published in Cyprus or were authored/published by Cypriots. The archive is Graphic Design related, type-centered and includes materials dating from the early 20th century until the late 1990s. This archive is an attempt to build an appreciation towards the local graphic design scene, writing its own design narrative, oriented for designers, book enthusiasts, writers, and the humanistic field. The presentation will also showcase a side project called TypeType which is a web-app for generating random texts, utilizing the letters that were found on book covers from the Cyprological Book Archive. It accesses a library of cut-out glyphs (letters, numbers and punctuations) to create an original mashed-up typographic synthesis.